Task success based on contingency fit of managerial culture and embeddedness - Ma, Li; Chen, Aihua; Zhang, Zhi-Xue (Journal of International Business Studies, 2016)
The article extends research on the contingency of fit in international management at the level of managerial tasks. Foreign firms’ managerial tasks are embedded in two environments with different profiles, and different managerial cultures fit them to ensure task success. Study 1 analyzes 18 critical incidents, summarizes Chinese and Japanese managerial cultures, and identifies three types of managerial tasks. We hypothesize that task success depends on the fit between task type and the chosen managerial culture, such that foreign firms can have their operational, local, and people tasks successfully completed using home, host, or integrated managerial cultures respectively. Study 2 tests our hypotheses using 112 critical incidents. The fit pattern at the level of managerial tasks advances the contingency perspective in international management and equips managers with cultural agility to confront international challenges.